2020
DOI: 10.3390/ijms21218157
|View full text |Cite
|
Sign up to set email alerts
|

ER–Mitochondria Contact Sites Reporters: Strengths and Weaknesses of the Available Approaches

Abstract: Organelle intercommunication represents a wide area of interest. Over the last few decades, increasing evidence has highlighted the importance of organelle contact sites in many biological processes including Ca2+ signaling, lipid biosynthesis, apoptosis, and autophagy but also their involvement in pathological conditions. ER–mitochondria tethering is one of the most investigated inter-organelle communications and it is differently modulated in response to several cellular conditions including, but not limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 120 publications
(154 reference statements)
0
36
1
Order By: Relevance
“…In the present study, we found that bevacizumab treatment is associated with intracellular calcium overload, ER stress, and caspase-12 activation, suggesting that ER stress contributes to bevacizumab-mediated cardiomyocyte damage. Notably, while our data do not establish a causal relationship between ER stress and mitochondrial dysfunction, many studies have reported that ER stress may contribute to mitochondrial damage [67]. We also did not explore the possibility of interactive effects between ER stress and mitochondrial dysfunction.…”
contrasting
confidence: 74%
“…In the present study, we found that bevacizumab treatment is associated with intracellular calcium overload, ER stress, and caspase-12 activation, suggesting that ER stress contributes to bevacizumab-mediated cardiomyocyte damage. Notably, while our data do not establish a causal relationship between ER stress and mitochondrial dysfunction, many studies have reported that ER stress may contribute to mitochondrial damage [67]. We also did not explore the possibility of interactive effects between ER stress and mitochondrial dysfunction.…”
contrasting
confidence: 74%
“…For example, the methods that allow us to study the dynamics of these contacts lack spatial resolution, and the methods that offer spatial resolution do not allow us to study dynamics since they usually require fixation of the sample. Current methods used to study MERCS have been recently described in several review articles, including those of Scorrano et al and Giamogante et al [ 11 , 259 ]. Therefore, further development of new tools to study MERCS will help us to better answer questions such as those related to the possibility of different types of MERCS and whether these MERCS have different proteomes and phospholipid/lipid compositions in the same cell type or in different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Here, by using a reverse approach, mainly based on TDP-43 silencing in HeLa cells and other genetic tools, including SPLICS probes for MERCs quantification [ 56 , 57 , 58 , 62 ], we demonstrated that TDP-43 down-regulation potently diminished both short- (~8–10 nm) and long-range (~40–50 nm) ER–mitochondria interactions. Importantly, by using the same SPLICS approach, we observed that MERCs density was not significantly perturbed by overexpressing either WT or ALS-related Q331K mutant TDP-43, which led to TDP-43 accumulation in cytotoxic inclusion bodies [ 63 ], thereby further suggesting a loss-of-function contribution of TDP-43 in MERCs disruption.…”
Section: Discussionmentioning
confidence: 99%
“…In the attempt to clarify whether TDP-43 loss of function disrupts ER–mitochondria cross-talk as a possible pathogenic mechanism in TDP-43 proteinopathies, in the present study, we analysed MERCs and ER–mitochondria Ca 2+ fluxes by different genetic approaches in HeLa cells. To this purpose, we down-regulated TDP-43 expression by an already validated targeted siRNA [ 55 ] and quantitatively analysed MERCs presence and ER–mitochondria Ca 2+ signalling using novel split green fluorescent protein-based contact site sensors (SPLICS) [ 56 , 57 , 58 ] and genetically targeted aequorin Ca 2+ probes, respectively, in comparison with control HeLa cells. The reported results suggest that TDP-43 participates in the maintenance of proper ER–mitochondrial signalling, possibly through the regulation of RNA metabolism and glycogen synthase kinase 3β (GSK3β) expression/activity.…”
Section: Introductionmentioning
confidence: 99%